Whole animal HTS of small molecules for antifungal compounds. (1st February 2016) - Muhammed, Maged; Arvanitis, Marios; Mylonakis, Eleftherios
ABSTRACT: Introduction : The high morbidity and mortality among patients with invasive fungal infections and the growing problem of fungal resistance have resulted in an urgent need for new antifungal agents. Areas covered : This review covers the importance of antifungal drug discovery with an emphasis on whole-animal high-throughput techniques. More specifically, the authors focus on Caenorhabditis elegans, as a substitute model host and discuss C. elegans as an alternative model host for the study of microbial pathogenesis and the identification of novel antifungal compounds. Expert opinion : There are significant advantages from using the substitute model host C. elegans in high-throughput drug discovery. The C. elegans- microbe model provides a whole animal system where host–pathogen interactions can be studied along with the evaluation of antimicrobial efficacy of compounds. This approach allows the study of compound characteristics, such as toxicity and solubility, during the initial screen and compounds discovered using C. elegans are affective in mammalian models.